THE EFFECTIVENESS OF DIRECT EXPENDITURE BUDGET ON PERFORMANCE - Nilawati Nasti; Ahmad Husin Lubis; Bakhtiar Bakhtiar; Abdul Rasyid Ms (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This paper described the implementation of the budget directly to the performance-based budget and analyzed it. The data source of this study from secondary data, namely data obtained from documents and archives obtained from the Medan Helvetia District Office. While the data collection techniques in this study were carried out by observation, interviews, and documentation studies. The data analysis technique used is a comparative descriptive analysis that uses the preparation of performance-based direct spending budgets set by the general bureau and secretarial equipment of Medan Helvetia Subdistrict. The results of the research obtained using the Budget and Expenditure of the Medan Helvetia Subdistrict Office are quite effective. Budget and spending effectiveness ratio from 2019 effectiveness ratio of 84.22%, in 2020 effectiveness ratio of 93.33%, in 2021 effectiveness ratio of 97.7%.